(untitled) (International Journal of Physiology, 2019)
Background One of the most common stress on human body is exercise. It places a major demand on the cardiopulmonary system. The most practical test of assessing the respiratory function is spirometry. The present study was carried out to know the effect of acute excercises on pulmonary function test in 90 1st year M. B. B. S. students (M=46, F=44). The changes in PFTs before and after acute exercise of 6 minutes (Harward’s step test) of those students were recorded. Results were analyzed using paired and unpaired t-test Results No significant changes were observed in all the four groups before and after exercise in males. However the post exercise values of FVC and VC were reduced than the baseline values in overweight and obese females (p < 0.01). Conclusion Acute exercise did not significantly affect the respiratory parameters. However the BMI of the individual may significantly influence the ventilatory response to acute exercise in otherwise healthy individuals.